Avaliação da prevalência de sintomas gastrointestinais e cardiovasculares em trabalhadores rurais expostos e não expostos à agrotóxicos no Vale de Cuncas, Barro-CE - Oliveira, Luciano Braga de (2017)
INTRODUCTION: The economic growth turned Brazil into one of the greatest agrochemicals consumers in the world. However, there were few studies that analyzed agricultural workers health exposure. OBJECTIVE: Evaluate the prevalence of cardiovascular symptoms on tomato rural workers (GE) exposed to agrochemicals in the Cuncas Valley, Barro ¿ CE. METHODS: A cross-sectional study questionnaire was applied to 50 tomato rural workers (GE), aged at least 18 years old, in their work place. A control group was selected from the not exposed population (GNE) paired by gender and age. It was used two questionnaires: a bio demographical, in order to analyze the schooling, income, marital status, residence type, medications and cardiovascular symptoms; and a protocol questionnaire about agrochemicals health effects to verify preparation steps, application, packaging destination, work clothes, use of Individual Protection Equipment (IPEs), perception and search for health services (hospitals or health basic units) in case of health alterations after agrochemicals application. It was applied a descriptive analysis, chi-square test, two proportion test and a logistic regression. The significant level was 5%. RESULTS: The exposed mean age was 41.42 (sd=10.50), and for the non-exposed group was 42.42 (sd=15.91). Ninety four percent was male, with some schooling. In the exposed group all tomato workers used agrochemicals, 66% not differ the toxicological products classification, only 22% read the packages. In relation to the agrochemicals, the same group, 94% used according to the recommended measures, 76% used daily, 98% used manual application and 78% avoid agrochemical overdose. Workers exposed to the agrochemicals presented more irritability (p<0.001), mental confusion (p=0.001), shortness of breath (p=0.003), sweating (p=0.008), dizziness (p=0.046), and headache (p=0.047). Rural workers exposed to agrochemicals had more chance to have a stomachache (RP=3.92, CI95%: 1.01 ¿ 15.22), chest pain (RP=5.33, CI95%: 1.68 ¿ 16.97), tachycardia (RP=4.48, CI95%: 1.34 ¿ 14.24), palpitation (RP=3.53, CI95%: 1.05 ¿ 11.86) and hypertension (RP=5.18, CI95%: 1.53 ¿ 17.99) when compared to the non-exposed group. In the exposed group the workers who did not give particular attention to clothes had more chance to developed hypertension (RP=5.70, CI95%: 1.01 ¿ 33.27) and cardiovascular disease (RP=5.40, CI95%: 1.01 ¿ 30.17). CONCLUSION: Exposure to agrochemicals affected the cardiovascular and gastric health system.